2019
DOI: 10.1038/s42005-019-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

Holographic vector field electron tomography of three-dimensional nanomagnets

Abstract: Complex 3D magnetic textures in nanomagnets exhibit rich physical properties, for example in their dynamic interaction with external fields and currents, and play an increasing role for current technological challenges such as energy-efficient memory devices. To study these magnetic nanostructures including their dependency on geometry, composition and crystallinity, a 3D characterization of the magnetic field with nanometer spatial resolution is indispensable. Here we show how holographic vector field electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 44 publications
0
41
0
1
Order By: Relevance
“…The overarching questions regarding magnetic sensing with ferromagnetic liquids is the detection of physical changes that is conveniently done by magneto-resistance measurements in exchange-coupled metallic materials. For these applications, electro-chemical plating using a porous alumina template and strain-engineering rolled-up nanotech facilitating intrinsic strain gradients have been employed [60,61] and refined to synthesize nano-rods, nano-tubes and multi-segmented specimens [64][65][66][67][68][69][70] with variable diameter (<50 nm), and microtubules with tailored magnetization configuration [71,72] that achieve unprecedented sensitivity based on the giant magneto-impedance effect [73].…”
Section: Technological Perspectivementioning
confidence: 99%
“…The overarching questions regarding magnetic sensing with ferromagnetic liquids is the detection of physical changes that is conveniently done by magneto-resistance measurements in exchange-coupled metallic materials. For these applications, electro-chemical plating using a porous alumina template and strain-engineering rolled-up nanotech facilitating intrinsic strain gradients have been employed [60,61] and refined to synthesize nano-rods, nano-tubes and multi-segmented specimens [64][65][66][67][68][69][70] with variable diameter (<50 nm), and microtubules with tailored magnetization configuration [71,72] that achieve unprecedented sensitivity based on the giant magneto-impedance effect [73].…”
Section: Technological Perspectivementioning
confidence: 99%
“…m) Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International license (https://creativecommons.org/licenses/ by/4.0). [292] Copyright 2015, The Authors, published by Wiley-VCH. n) Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International license (https://creativecommons.org/licenses/by/4.0).…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Complementary, hard X-ray magnetic tomography with ptychographic scans potentially allows for 10 nm resolution of 3D magnetic textures, [291] see Figure 8l. The electron holography is extended to holographic vector field electron tomography, [292,324] see Figure 8m, that allows to reconstruct 3D magnetic textures with a sub 10 nm resolution.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The authors argued that the method is applicable to practical magnetic materials and can be extended to 3D visualization of the magnetic domain formation process under external magnetic fields. Very recently, Wolf et al [188] have shown the 3D magnetic induction mapping of a layered Cu/Co nanowire after reconstruction of both the magnetic induction vector field and 3D chemical composition of the material with sub-10 nm spatial resolution using the holographic vector field electron tomography approach.…”
Section: D Imaging Of Magnetic Domainsmentioning
confidence: 99%